Experimental research of the failure mechanisms of sandwich specimens with facing layers from unidirectional - S.A. Kholmogorov; N.V. Levshonkova (Учёные записки Казанского университета: Серия Физико-математические науки)
An experimental technique was developed for the compression testing of sandwich specimens with thin fiber-reinforced composite facing layers. It assumes that thin layers of a composite material are tested, and their specimens, even with a very short gage length, become unstable, thereby distorting the ultimate stress value. Here, we discuss the results of our experimental studies of the failure mechanisms of sandwich specimens with facing layers having [0°] lay-up under axial compression. It was revealed that the shear buckling mode is possible in specimens with different geometrical parameters so that the ultimate stress formed in the facing layers can be taken as a mechanical characteristic when calculating the strength of composite structures. It was shown that an in-phase flexural buckling mode occurs under compression of specimens having a honeycomb core in their facing layers. A non-classical shear buckling mode is only possible in specimens with a rigid balsa core.